Therapeutic and cosmeceutical potential of ethosomes: An overview - Poonam Verma; K Pathak (Wolters Kluwer Medknow Publications, 2010)
The main disadvantage of transdermal drug delivery is the poor penetration of most compounds into the human skin. The main barrier of the skin is located within its uppermost layer, the stratum corneum (SC). Several approaches have been developed to weaken this skin barrier. One of the approaches for increasing the skin penetration of drugs and many cosmetic chemicals is the use of vesicular systems, such as, liposomes and ethosomes. Ethosomes are phospholipid-based elastic nanovesicles containing a high content of ethanol (20-45%). Ethanol is known as an efficient permeation enhancer and has been added in the vesicular systems to prepare elastic nanovesicles. It can interact with the polar head group region of the lipid molecules, resulting in the reduction of the melting point of the stratum corneum lipid, thereby increasing lipid fluidity and cell membrane permeability. The high flexibility of vesicular membranes from the added ethanol permits the elastic vesicles to squeeze themselves through the pores, which are much smaller than their diameters. Ethosomal systems are much more efficient in delivering substances to the skin in the terms of quantity and depth, than either conventional liposomes or hydroalcoholic solutions. The scope of this small review is to introduce the novel concept of ethosomes and to describe some approaches and mechanisms of stimulating topical and transdermal products with ethosomes.